Pengelolaan Pembiayaan Pendidikan di MTs Al-Ikhlas Campaka - Moh Sugandi; Susanti Susanti (MANAZHIM, 2019)
MTs Al-Ikhlas has income derived from BOS and student information. Based on the results of an exploratory study in MTs Al-Ikhlas madrasa financing management, MTs Al-Ikhlas was considered less effective in managing madrasa finance. aims to describe education funding planning, Describe the implementation of education funding, Describe financing responsibilities, Describe. Data collection techniques using interview techniques, observation and documentation. Funding Management in MTs Al-Ikhlas Campaka is carried out by process: Budgeting (Budget planning): Financing financing has been carried out properly and transparently, Source of Funding is obtained from several sources namely: source of funds from the community (SPP), sources of funding from the government in the form of BOS funds , The implementation of the financing based on the budget that has been made (RKAS), the supervision and accountability of funding is carried out by the principal and the foundation. Funding management has been carried out transparently, effectively and efficiently. When planning involves parties who represent the parts in school. Funding management is also still lacking, not all posts are stated in the RKAS, because there are still expenditures outside the RKAS for the KBM smoothness process. Supporting and Inhibiting Factors. Supporting factors in financing management: schools have the right to regulate school funding according to school needs without being totally dependent on the foundation. Inhibiting factors in financing management: non-current funding sources, both BOS funding and student delays in SPP payments.